Nilai-Nilai Karakter dalam Cerita Rakyat si Pogos-Pogos Masyarakat Batak Toba - Tompul, Tania; Saragih, Dinda Apriani; Hutauruk, Febri Ola; Sari, Indah; Sibarani, Tomson (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
Folktales are oral expressions of local culture that are transmitted from generation to generation. This study aims to analyze the values of local wisdom contained in folk tales, focusing on the aspects of peace and prosperity as well as their meaning and function according to Sibarani's perspective. The research method used is descriptive qualitative, with data collection techniques including literature study, observation, and recording. This study uses the theory of local wisdom developed by Robert Sibarani. The results of the study identify the values intended to teach morals or norms for community life, and these values play a role in the values of hard work, caring, and social solidarity that reflect the character of the local community as well as the meaning and function of each of the values contained therein. Based on the explanation of the values in the story above, the researcher was interested in describing all the values in this story so that they could be preserved. The story si Pogos-Pogos tells of a man who managed to change his life from poor to rich and successful through hard work, honesty, and good attitude. These values can be revitalized and preserved by the younger generation as part of the formation of a positive cultural character.